Analisis Kinerja Keuangan Pada PT. Unilever Indonesia Tbk. yang Terdaftar Di Bursa Efek Indonesia (BEI) - Salsabila Maulyawati M; Yusra Nginang; Asniwati (Sekolah Tinggi Ilmu Manajemen Indonesia YAPMI, 2025)
Financial report analysis is one way to find out a company's performance in a period. This research aims to determine the financial performance of PT. Unilever Indonesia Tbk. This type of research was quantitative research. The data used was secondary data. The population and sample were the financial reports of PT. Unilever Indonesia Tbk. in a balance sheet and profit and loss form for the 2019-2023 period. Data collection used documentation techniques, was the evidence of PT's financial reports. Unilever Indonesia Tbk. Financial performance analysis tools were in the form of financial ratios, namely liquidity ratios, solvency ratios, activity ratios and profitability ratios. Research results of liquidity ratios based on the company's current ratio and quick ratio were in